2011
DOI: 10.1038/ejhg.2011.238
|View full text |Cite
|
Sign up to set email alerts
|

The novel mitochondrial tRNAAsn gene mutation m.5709T>C produces ophthalmoparesis and respiratory impairment

Abstract: Although mutations in mitochondrial tRNAs constitute the most common mtDNA defect, the presence of pathological variants in mitochondrial tRNA Asn is extremely rare. We were able to identify a novel mtDNA tRNA Asn gene pathogenic mutation associated with a myopathic phenotype and a previously unreported respiratory impairment. Our proband is an adult woman with ophthalmoparesis and respiratory impairment. Her muscle biopsy presented several cytochrome c oxidase-negative (COXÀ) fibres and signs of mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Nine different point mutations in MT ‐ TN have previously been reported to be associated with mitochondrial disease. Five of these appeared as isolated PEO with mitochondrial myopathy without demonstrated inheritance 2–4,7–10,13 . Together with the two mutations described here, seven out of eleven mutations show this phenotype, which is otherwise associated mainly with large‐scale deletions of mtDNA.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Nine different point mutations in MT ‐ TN have previously been reported to be associated with mitochondrial disease. Five of these appeared as isolated PEO with mitochondrial myopathy without demonstrated inheritance 2–4,7–10,13 . Together with the two mutations described here, seven out of eleven mutations show this phenotype, which is otherwise associated mainly with large‐scale deletions of mtDNA.…”
Section: Discussionmentioning
confidence: 61%
“…We identified two mtDNA mutations, m.5669G>A and m.5702delA, in the MT ‐ TN gene, encoding the tRNA Asn and demonstrated their pathogenicity. Nine probably pathogenic mutations have previously been described in the MT ‐ TN gene 2–14 . Five of these were associated with sporadic PEO, which together with the two mutations described here makes the MT ‐ TN gene a hot spot for sporadic PEO associated with mtDNA point mutations.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Mitochondrially localized aaRSs (mit-aaRS) have been of considerable clinical interest since mutations have been identified that cause distinctive disease phenotypes dependent on the particular mit-aaRS. The last two decades have accumulated both clinical and diagnostic data, indicating that mutations in either the substrate mit-tRNA or in the mitochondrial aaRS can lead to diverse presentations of mitochondrial disease [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. More than 200 point mutations have been identified in mitochondrial genes, the vast majority of which are associated with diverse forms of neurological diseases [20][21][22].…”
Section: Introductionmentioning
confidence: 99%